Antibody response in naïve and sensitised goats infested by Sarcoptes scabiei - Simson Tarigan (Jurnal Ilmu Ternak dan Veteriner, 2004)
The purpose of this study was to characterize the IgG and IgE antibody responses in goats infested repeatedly with Sarcoptes scabiei. Ten goats purchased from scabies-free farms were infested with 2000 live mites on the auricles. Fifty days after the initial infestation, the goats were treated with ivermectin. After being completely recovered, the goats were reinfested then treated again at 50 days post infestation. Blood samples were collected at the time of the first infestation, then every 10 days afterwards for 270 days. Seroconversion for IgG took place after 30 days following the first infestation, whereas the maximum level of the specific IgG antibodies occurred after 50 days. Immunoblot analysis identified a number of antigens (Mr 180, 135, 43 and 38 KDa) that recognised by the IgG at 10 days and continuously recognised throughout the course of the multiple infestations. Being consistently recognised, those antigens should be essential in the development immunological diagnostic tests for scabies. The levels of scabies-specific IgE antibodies increased slowly during the first infestation and rapidly dropped following treatment of the animals with ivermectin. In the second and third infestations, however, the reaginic antibodies rose rapidly and with a grater level. On immunoblot analysis, at least 10 antigens (Mr 130, 72, 64, 58, 48, 44, 41, 39, 27 and 25 KDa) were observed to be recognised by the IgE present in the sera from scabies-infested animals. Since IgE response is considered to play a major role in the immune protection, those allergens, therefore, could be used as the main component of an anti-scabies vaccine.   Key words: Sarcoptes scabiei, antibody, goats